Luciferase-tagged wild-type and tropism-deficient mouse cytomegaloviruses reveal early dynamics of host colonization following peripheral challenge - Farrell, Helen; Oliveira, Martha; Macdonald, Kate; Yunis, Joseph; Mach, Michael; Bruce, Kimberley; Stevenson, Philip; Cardin, Rhonda; Davis-Poynter, Nicholas (Journal of General Virology, 2016)
Cytomegaloviruses (CMVs) establish persistent, systemic infections and cause disease by maternal-foetal transfer, suggesting that their dissemination is a key target for antiviral intervention. Late clinical presentation has meant that human CMV (HCMV) dissemination is not well understood. Murine CMV (MCMV) provides a tractable model. Whole mouse imaging of virus-expressed luciferase has proved a useful way to track systemic infections. MCMV, in which the abundant lytic gene M78 was luciferase-tagged via a self-cleaving peptide (M78-LUC), allowed serial, unbiased imaging of systemic and peripheral infection without significant virus attenuation. Ex vivo luciferase imaging showed greater sensitivity than plaque assay, and revealed both well-known infection sites (the lungs, lymph nodes, salivary glands, liver, spleen and pancreas) and less explored sites (the bone marrow and upper respiratory tract). We applied luciferase imaging to tracking MCMV lacking M33, a chemokine receptor conserved in HCMV and a proposed anti-viral drug target. M33-deficient M78-LUC colonized normally in peripheral sites and local draining lymph nodes but spread poorly to the salivary gland, suggesting a defect in vascular transport consistent with properties of a chemokine receptor.
EVALuna2:8326